1996
DOI: 10.1111/j.1469-8137.1996.tb01912.x
|View full text |Cite
|
Sign up to set email alerts
|

Facilitation of plant phosphate acquisition by arbuscular mycotrhizas from enriched soil patches

Abstract: S U M M h R YMycorrhizal contribution to nutrient acquisition from spatially heterogeneous soil was investigated using two-way comparisons of non-mycorrhizal and arbuscular mycorrhizal Agropyron desertorum (Fisch. ex Link) Schult. in soil with either a patchy or a uniform nutrient distribution. Double-labelling allowed a comparison between acquisition of an ion of lower abundance and mobility, phosphate (P), and an ion of higher abundance and mobility, nitrate. As expected, root density increased in enriched-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 31 publications
3
47
0
Order By: Relevance
“…Repression of root growth in the presence of an organic patch has been demonstrated previously by Hodge et al (1998). Cui & Caldwell (1996) reported that proliferation of Agropyron desertorum roots in nutrient-rich patches decreased when colonized by AM fungi, although the difference was only weakly significant (P l 0.07). By contrast, in our study the reverse was observed ; addition of a mycorrhizal inoculum enhanced proliferation within an organic patch.…”
Section: Root Proliferationsupporting
confidence: 67%
“…Repression of root growth in the presence of an organic patch has been demonstrated previously by Hodge et al (1998). Cui & Caldwell (1996) reported that proliferation of Agropyron desertorum roots in nutrient-rich patches decreased when colonized by AM fungi, although the difference was only weakly significant (P l 0.07). By contrast, in our study the reverse was observed ; addition of a mycorrhizal inoculum enhanced proliferation within an organic patch.…”
Section: Root Proliferationsupporting
confidence: 67%
“…In the accompanying study (Cui & Caldwell, 1996), mycorrhizal roots of Agropyron desertorujn were quite effective in exploiting P from enriched patches. The present work addresses how effectively the hyphae can exploit nutrient-rich patches several centimetres distant from the roots.…”
Section: Introductionmentioning
confidence: 82%
“…Field soil was collected and sterilized as described previously (Cui & Caldwell, 1996). Sixteen kg of dry soil were placed in the outer compartment of each container, and 0-4 kg in the central compartment.…”
Section: Soil and Initial Nutrient Patternsmentioning
confidence: 99%
“…Therefore, mycorrhiza increases phosphorus uptake by plant roots under drought stress and without stress (Hetrick et al, 1996). Phosphorus uptake increased by absorption from roots (Smith and Read, 1997;Cui and Caldwell, 1996). The symbiosis with the G. intraradices fungus in pepper resulted in an increase in leaf area ratio, which is due to mycorrhizal effect on increasing phosphorus content in this plant (Demir, 2004).…”
Section: Figure 24 Effect Of Drought Stress Levels On Na Concentrationmentioning
confidence: 99%